Intravascular ultrasound-guided emergency coronary Palmaz-Schatz stent placement without post-procedural systemic anticoagulation. Issue 4 (October 1996) - Blasini, R.; Neumann, F. J.; Richardt, G.; Schmitt, C.; Paloncy, R.; Schömig, A.
Abstract : OBJECTIVE: To test the efficacy of intravascular ultrasound (IVUS)-guided stent placement and to determine the clinical outcome during the first 30 days in those patients who were treated with antiplatelet therapy rather than anticoagulants because they met the IVUS criteria for optimal stent placement. DESIGN: Prospective observational study. PATIENTS: 126 patients with successful, non-elective Palmaz-Schatz stent placement. INTERVENTIONS: IVUS was performed to assess the attachment of stent struts, the coverage of the dissection, and the intrastent minimal lumen area. MAIN OUTCOME MEASURES: Intrastent lumen area, clinical outcome during the first 30 days. RESULTS: In all patients IVUS showed complete apposition and coverage of the dissection. In 23 patients (18%) the IVUS lumen area criterion was achieved. In 75 patients, further balloon dilatation was performed and in 41 IVUS criteria were finally fulfilled. The minimal intrastent lumen area increased from a mean (SD) of 6.81 (1.15) mm2 to 9.56 (2.61) mm2 (P < or = 0.01) between the first and final IVUS investigations. 64 patients (51%) who met the IVUS criteria were treated with aspirin (100 mg) and ticlopidine (250 mg) twice a day. During the first 30 days none of the following events occurred: death, myocardial infarction, repeat intervention, aortocoronary bypass surgery, and subacute stent thrombosis. CONCLUSION: The additional information provided by IVUS examination helped the operator to decide whether further dilatation was needed after a coronary stent had been placed. For patients who met the IVUS criteria for optimal stent placement, antiplatelet therapy was associated with an excellent clinical outcome during the first 30 days.